2023
DOI: 10.1093/forestry/cpad010
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and successional trends of woody vegetation in seasonally dry tropical forests

Abstract: Understanding the recovery time of vegetation structure and species composition to estimate the resilience of seasonally deciduous tropical forest (SDTF) is fundamental for conservation actions. Related information is still scarce for the semi-arid Brazilian SDTF (locally called Caatinga), which covers more than 800 000 km2 in the northeast of Brazil. We aimed to estimate how long it takes for 11 attributes of vegetation structure and species composition, separately and aggregated, to become similar to an old-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…This supports our results in SEM calculations and could explain why the AGB is higher in suction pumping mining forest stands. The positive relationship between AGB and tree species diversity found in suction pumping mining forest stands of the present study was reported by other studies in secondary forests [60,83,84] and old-growth forests [24,58,76,80,85]. Because of forest woody productivity, it is usually positively associated with tree species diversity [85].…”
Section: Effects Of Mining Type Stand Age and Distance From The Fores...supporting
confidence: 88%
See 4 more Smart Citations
“…This supports our results in SEM calculations and could explain why the AGB is higher in suction pumping mining forest stands. The positive relationship between AGB and tree species diversity found in suction pumping mining forest stands of the present study was reported by other studies in secondary forests [60,83,84] and old-growth forests [24,58,76,80,85]. Because of forest woody productivity, it is usually positively associated with tree species diversity [85].…”
Section: Effects Of Mining Type Stand Age and Distance From The Fores...supporting
confidence: 88%
“…In our study, the dynamics of the slow recovery of species follow the "initial floristic composition model" hypothesis [100], because the dominance (IVI) is relayed from one floristic group (species, genus or family) to another throughout the chronosequence [97]. This hypothesis states that pioneer species colonize early successional stages which remain for some decades [76], and soon they make suitable conditions for colonization by other species more typical of later successional stages [97]. A similar pattern was found in other secondary successions post mining in the Peruvian Amazon [41,41].…”
Section: Tree Species Dominance and Compositionmentioning
confidence: 62%
See 3 more Smart Citations